2006
DOI: 10.1177/0954008306055011
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Hydroxyl Terminated Polybutadiene Toughened Phenolic Resin

Abstract: Phenolic novolac was modified with hydroxyl terminated polybutadiene (HTPB) using resole as compatibilizer. These systems were characterized by differential scanning calorimetry, and IR analysis. Neat resin castings were prepared with varying percentages of HTPB. The fracture toughness of these systems was assessed by evaluating the critical stress intensity factor (K Ic ) using single-edge notch, threepoint bend specimens. The fracture behavior was characterized by scanning electron microscopy. These studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The peak at 2.71 ppm was attributed to the appearance of the methine resonance due to the proton attached to the oxirane ring (CH 5 ). These results were in agreement with those of recent work by Yokshan and Hamzah et al The similarity of these spectra with those of NR confirmed that the cis −1,4‐polyisoprene structure was retained in the liquid NR …”
Section: Resultssupporting
confidence: 93%
“…The peak at 2.71 ppm was attributed to the appearance of the methine resonance due to the proton attached to the oxirane ring (CH 5 ). These results were in agreement with those of recent work by Yokshan and Hamzah et al The similarity of these spectra with those of NR confirmed that the cis −1,4‐polyisoprene structure was retained in the liquid NR …”
Section: Resultssupporting
confidence: 93%
“…12,13 The hydroxyl-terminated polybutadiene (HTPB) is the most popular polyol applied in recent years. 14 This liquid prepolymer has outstanding physical characteristics including the low temperature of glass transition, high tensile ability, and strong chemical resistance. 14,15 HTPB-based propellants have distinct advantages such as very high reliability, good processing, and unequaled mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 There are numerous ways to modify novolac resin. [3][4][5][6] One common way is to develop addition-cure phenolics, [7][8][9][10][11][12][13][14][15] including the introduction of allyl groups, maleimide groups, phenylethynyl groups, epoxy groups, benzoxazoline structure, benzoxazine structure, phenoltriazine structure, arylacetylene groups, phthalonitrile groups, ethynyl phenyl azo groups, and propargyl ether groups (propargylated novolac (PN) resins). Bindu et al 16 and Wang et al 17 have particularly investigated PN resins, and cured PN resins show improved thermal properties compared with the original novolac resin.…”
Section: Introductionmentioning
confidence: 99%